Antioxidant capacity and phenolics of spray dried Arrenga pinnata juice powder - Badmus, Abdurrahman Adeleye; Yusof, Yus Aniza; Chin, Nyuk Ling; A. Aziz, N. (Faculty of Engineering, Universiti Putra Malaysia, 2016)
The ferric reducing antioxidant power, total phenolic content, radical scavenging activity, amino acid content and sugar content of spray dried arrenga pinnata juice powder was evaluated to determine the quality of spray dried powder obtained by spray drying of fresh arrenga pinnata juice at inlet temperature of 130°C, feed flow rate of 350ml/h, outlet temperature of 70°C and maltodextrin 10DE addition at 20%. Powder obtained has a total phenolic compounds content of 5.82 mg/100g of GAE and antioxidant potential identified by free radical scavenging activity (IC50) of 0.6mg/ml. The total sugar content of arrenga pinnata powder resulted in 30.14%. The analysis of free amino acids depicted the presence of lysine, glutamic acid, aspartic acid and alanine in higher levels. The homogenous and spherical nutritious particles can easily be reconstituted into juice.